When the original is beyond reach: consumer perception and demand for counterfeit luxury goods in Germany and South Korea. (2015) - Hennigs, Nadine; Wiedmann, Klaus-Peter; Klarmann, Christiane; Behrens, Stefan; Jung, Jaehee; Hwang, Choon Sup
The tremendous growth in the luxury market in the last decades has been accompanied by a prevalence of pirated and counterfeit goods. Reasoning that all governmental efforts and management actions to curtail counterfeit activities will not be sufficient as long as counterfeiters face such an immense demand for their products, the importance of focusing on the consumer perspective becomes evident. In this context, the aim of this study is to provide and empirically investigate a comprehensive framework of the consumer demand for counterfeit luxury goods. Based on theoretical and empirical insights on the acceptance of counterfeits in different markets, we propose a model of determinants that influence the trade-off between genuine and counterfeit luxury goods from a consumer's perspective. The comparison of empirical data from Germany and South Korea reveal the significant impact of psychological and context-related antecedents on counterfeit perception and counterfeit shopping behaviour. The selected countries offer interesting insights in the consumer perspective on counterfeits as they provide distinct socio-cultural contexts and represent both the demand for authentic luxury brands as well as for counterfeit goods.